Natural diet of Neohelice granulata (Dana, 1851) (Crustacea, Varunidae) in two salt marshes of the estuarine region of the Lagoa dos Patos lagoon - Barutot,Roberta Araujo (2011)
Natural diet of Neohelice granulata in two salt marshes of Lagoa dos Patos, RS were studied. Sampling was performed seasonally and crabs were captured by hand by three persons during one hour, fixed in formaldehyde (4%) during 24 h, transferred to alcohol (70%). Each foregut was weighed and repletion level was determined. Differences between sexes in the frequencies of occurrence of items were tested by χ2test. A total of 452 guts were analyzed. Quali-quantitative analyses were calculated following the method of relative frequency occurrence and relative frequency of the points. At both sites, for both sexes and in all seasons, the main food items were sediment, Spartina sp. and plant detritus. The highest values of mean repletion index were estimated for the spring and summer. Analysing both salt marshes, in different seasons significant shifts in the natural diet of Neohelice granulata was not observed throughout the period of study.